2013
DOI: 10.1038/jes.2013.72
|View full text |Cite
|
Sign up to set email alerts
|

Weather and triggering of ventricular arrhythmias in patients with implantable cardioverter-defibrillators

Abstract: Outdoor ambient weather has been hypothesized to be responsible for the seasonal distribution of cardiac arrhythmias. Because people spend most of their time indoors, we hypothesized that weather-related arrhythmia risk would be better estimated using an indoor measure or an outdoor measure that correlates well with indoor conditions, such as absolute humidity. The clinical records of 203 patients in eastern Massachusetts, USA, with an implantable cardioverter-defibrillator were abstracted for arrhythmias betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…In the same cohort the authors found a nonlinear association between outdoor temperature and ventricular arrhythmias, with lower temperature and drier air were associated with increased risk of ventricular arrhythmia onset (Nguyen et al, 2013). Similarly, in another study of implanted cardiac defibrillators and daily outdoor temperatures McGuinn et al found a negative association between outdoor temperature and ventricular arrhythmias (McGuinn et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the same cohort the authors found a nonlinear association between outdoor temperature and ventricular arrhythmias, with lower temperature and drier air were associated with increased risk of ventricular arrhythmia onset (Nguyen et al, 2013). Similarly, in another study of implanted cardiac defibrillators and daily outdoor temperatures McGuinn et al found a negative association between outdoor temperature and ventricular arrhythmias (McGuinn et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…Increased mortality has been linked not only to heat wave episodes (Kaiser et al, 2007; Le Tertre et al, 2006; Ostro et al, 2009), but also to exposure to colder weather conditions (Analitis et al, 2008; Lee et al, 2014). These studies focused on hospital admissions or mortality, while fewer studies have investigated patient’s specific onset of arrhythmia (Nguyen et al, 2013; Nguyen et al, 2015; McGuinn et al, 2013). Some studies showed that chronic disease including cardiovascular disease, diabetes mellitus, mental illness, but also sociodemographic characteristics, and social isolation may heighten susceptibility to temperature-related mortality (Basu, 2009; O’Neill et al, 2003; Zanobetti et al, 2013), and that even without known chronic medical conditions, aging may increase susceptibility to the cardiovascular effects of temperature extremes and changes in temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Further complicating the interpretation of these results is the fact that outdoor and indoor temperatures in Boston correlate weakly in the colder months because of universal home heating. 28 Nguyen et al 29 found a nonlinear association between outdoor temperature and ventricular arrhythmias in a cohort of patients implanted with cardioverter-defibrillators living in Boston, which they attributed to the poor correlation between outdoor and indoor temperatures during the winter months. It is possible that the current study did not have sufficient power to detect a nonlinear association for temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Comprising all residents of New York City, US, this study reported that summer-time high temperatures were associated with reduced risk of hypertension-related hospital admissions, but it did not evaluate any possible effect from cold temperatures. The impact of temperatures on diabetes 15 16 17 and arrhythmia 18 19 , two conditions that often co-exist 20 21 22 23 24 with hypertension and share similar risk factors 25 , have been assessed in a handful of studies. A positive relationship between diabetes-related hospital admissions and apparent temperature (a composite index of temperature and humidity) was found in California, US 15 .…”
mentioning
confidence: 99%
“…The relationship between diabetes hospitalizations and heat waves was also investigated in two other studies, with a positive association reported in one study 16 but null association in another 17 . More recently, two panel studies of patients implanted with cardioverter-defibrillator devices reported that cold temperatures may trigger arrhythmia 18 19 .…”
mentioning
confidence: 99%